2013
DOI: 10.1136/heartjnl-2013-304449
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gender and age on occurrence of clinically suspected myocarditis in adulthood

Abstract: Men are significantly more susceptible to myocarditis than women. Young men are especially at risk for acquiring myocarditis, while women are affected most commonly at the postmenopausal age. The proportion of hospital admissions caused by myocarditis has an inverse, logarithmic association with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
85
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 29 publications
12
85
0
5
Order By: Relevance
“…For example, we show that advanced HF from myocarditis occurs mostly in young male patients. These age and sex differences are consistent with previous reports, where myocarditis has been shown to affect younger patients [12][13][14] and to be linked to male sex hormones. 6,15 The diagnosis of myocarditis was associated with higher acuity at listing, evidenced by a 10-fold higher requirement for biventricular MCS, 5-fold higher requirement for ECMO, and 3-fold higher requirement for ventilator need.…”
Section: Discussionsupporting
confidence: 82%
“…For example, we show that advanced HF from myocarditis occurs mostly in young male patients. These age and sex differences are consistent with previous reports, where myocarditis has been shown to affect younger patients [12][13][14] and to be linked to male sex hormones. 6,15 The diagnosis of myocarditis was associated with higher acuity at listing, evidenced by a 10-fold higher requirement for biventricular MCS, 5-fold higher requirement for ECMO, and 3-fold higher requirement for ventilator need.…”
Section: Discussionsupporting
confidence: 82%
“…discovered that myocarditis was more common in men (76.61%; 95% CI 75.11–78.05%) than in women (23.39%; 95% CI : 21.95–24.89%, P < 0.0001) and that men are significantly more susceptible to myocarditis than women. [20] In addition, the authors of another study found that women with myocarditis were more likely to develop ventricular arrhythmias than men with myocarditis ( OR = 2.43, 95% CI : 1.12–5.27) and that women possessed longer QT intervals, as demonstrated by electrocardiography, due to decreases in the expression levels of some pivotal proteins. [21] Moreover, myocarditis prolongs ventricular repolarization times in approximately 70% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of readily available sensitive and specific clinical diagnostic tests, wide variation in diagnostic criteria, and selected patient populations among published studies have hampered accurate estimations of epidemiology and natural history of myocarditis. According to experimental and clinical studies, however, young male adolescents and adults are considered most susceptible to viral myocarditis . In children, all ages from newborns to adolescents are affected, but 2 incidence peaks have been shown to occur: in infants aged <1 year and in teenagers …”
mentioning
confidence: 99%